Breast Care for Pregnant Women to Increase Mother's Milk Production in the Working Area of the Lotang Salo Health Center - Parwati, Dewi; Hasibuan, Evis Ritawani; Ambarawati, Eny Retna; Reffita, Lea Ingne; Mansur, Tri Novianty; Ula, Zumrotul (International Journal of Health Sciences, 2023)
Breast care for pregnant women that has been carried out so far is still oriented towards providing counseling or in other words, the emphasis is more on increasing knowledge and not specifically on implementation, nor has an evaluation been carried out on the results of post-counseling knowledge absorption so it is difficult to measure and assess how much application of their knowledge of breast care. This study aims to determine the effect of breast care on increasing breast milk production in Post Partum mothers at the Lotang Salo Sidrap Health Center. The results of the study show that 95% of 20 pregnant women performed breast care in the form of Breast Exercise/Breast Massage, pregnant women who underwent breast care. Her breast milk comes out smoothly at 95%. Results Daily breast milk production on the first day was 10-30 cc/day in 8 people (40%) and 20-40 cc/day was also in 8 people (40%), on the second day breast milk production was 40-60 cc/day in 10 people (50%), while on the third day breast milk production increased to 60-80 cc/day in 15 people (75%). The results of the study also showed that 15 pregnant women who did not take care of their breasts had poor milk production (75%) and 5 people (25%) did not produce breast milk. From the results of this research, it was concluded that pregnant women prefer breast care with breast massage; Breast Care with Breast Exercises/Breast Massage produces smoother milk production; Pregnant women who perform breast care have a significant effect on increasing breast milk production.